Nucleophilic catalysis of p-substituted aniline derivatives in acylhydrazone formation and exchange. Issue 33 (13th August 2021) - Canal-Martín, Andrea; Navo, Claudio D.; Sáez, Elena; Molero, Dolores; Jiménez-Osés, Gonzalo; Pérez-Fernández, Ruth
Abstract : Mechanistic study and superior performance of electron-rich  p -substituted aniline derivatives as catalysts for efficient hydrazone formation and exchange in both protic and aprotic solvents. Abstract : Hydrazone bond formation is a versatile reaction employed in several research fields. It is one of the most popular reversible reactions in dynamic combinatorial chemistry. Under physiological conditions, hydrazone exchange benefits from the addition of a nucleophilic catalyst. We report a mechanistic study and superior performance of electron-rich p -substituted aniline derivatives as catalysts for efficient hydrazone formation and exchange in both protic and aprotic solvents. Rigorous kinetic analyses demonstrate that imine formation with 3-hydroxy-4-nitrobenzaldehyde and aniline derivatives proceeds with unprecedented third-order kinetics in which the aldehyde consistently shows a partial order of two. Computational investigations provide insights into the mechanisms of these transformations.